The culture and development agenda in Lusophone Africa - Freitas, Raquel (2014)
The international discourse around development aid proposes the instrumentalisation of culture based on a positively valued utilitarian objective that is social and economic development. A public policy approach would expect this to be consensual among observers, but it is not, as there are potential negative impacts of such instrumentalisation and discussion is polarized. The interest of this paper is on what model, if any, of cultural policy is being diffused to developing countries and what leeway for policy choice is contained in such agenda. I propose to explore how the link between culture and development is framed in the interaction between international partners such as UNESCO and the EU, and three lusophone African countries: Angola, Mozambique and Cape Verde.